The Brain Drain and Underdevelopment: A Study of Emigration from Jamaica and Trinidad and Tobago to Canada - Hutchinson, Carlyle J. (My University, 1977)
The brain-drain from Jamaica and Trinidad and Tobago to Canada, constitutes one of the most serious, though often overlooked aspects of the overall underdevelopment of these two Caribbean countries.
More specifically, Canada's immigration policies have played a major part in creating and maintaining this highly-selective outflow of wrokers from the region.
The net effects of the drain can be seen in the social and economic distortions it creates in the West Indies, while at the same time contributing to the economic and social well-being of Canada.
The underdevelopment of these countries, inlcuding the brain drain, can end only by the coming into being of new political mechanims aimed at placing their politial economies at the commnad of the local populations.
Keywords: Political Science; Political Science